Chemoimmunotherapy with methotrexate, cytarabine, thiotepa, and rituximab (MATRix regimen) in patients with primary CNS lymphoma: results of the first randomisation of the International Extranodal Lymphoma Study Group-32 (IELSG32) phase 2 trial. Issue 5 (May 2016) - Ferreri, Andrés J M; Cwynarski, Kate; Pulczynski, Elisa; Ponzoni, Maurilio; Deckert, Martina; Politi, Letterio S; Torri, Valter; Fox, Christopher P; Rosée, Paul La; Schorb, Elisabeth; Ambrosetti, Achille; Roth, Alexander; et al.
Summary: Background: Standard treatment for patients with primary CNS lymphoma remains to be defined. Active therapies are often associated with increased risk of haematological or neurological toxicity. In this trial, we addressed the tolerability and efficacy of adding rituximab with or without thiotepa to methotrexate–cytarabine combination therapy (the MATRix regimen), followed by a second randomisation comparing consolidation with whole-brain radiotherapy or autologous stem cell transplantation in patients with primary CNS lymphoma. We report the results of the first randomisation in this Article. Methods: For the international randomised phase 2 International Extranodal Lymphoma Study Group-32 (IELSG32) trial, HIV-negative patients (aged 18–70 years) with newly diagnosed primary CNS lymphoma and measurable disease were enrolled from 53 cancer centres in five European countries (Denmark, Germany, Italy, Switzerland, and the UK) and randomly assigned (1:1:1) to receive four courses of methotrexate 3·5 g/m 2 on day 1 plus cytarabine 2 g/m 2 twice daily on days 2 and 3 (group A); or the same combination plus two doses of rituximab 375 mg/m 2 on days −5 and 0 (group B); or the same methotrexate–cytarabine–rituximab combination plus thiotepa 30 mg/m 2 on day 4 (group C), with the three groups repeating treatment every 3 weeks. Patients with responsive or stable disease after the first stage were then randomly allocated between whole-brain radiotherapy and autologous stem cell transplantation. A permuted blocks randomised design (block size four) was used for both randomisations, and a computer-generated randomisation list was used within each stratum to preserve allocation concealment. Randomisation was stratified by IELSG risk score (low vs intermediate vs high). No masking after assignment to intervention was used. The primary endpoint of the first randomisation was the complete remission rate, analysed by modified intention to treat. This study is registered withClinicalTrials.gov, numberNCT01011920 . Findings: Between Feb 19, 2010, and Aug 27, 2014, 227 eligible patients were recruited. 219 of these 227 enrolled patients were assessable. At median follow-up of 30 months (IQR 22–38), patients treated with rituximab and thiotepa had a complete remission rate of 49% (95% CI 38–60), compared with 23% (14–31) of those treated with methotrexate–cytarabine alone (hazard ratio 0·46, 95% CI 0·28–0·74) and 30% (21–42) of those treated with methotrexate–cytarabine plus rituximab (0·61, 0·40–0·94). Grade 4 haematological toxicity was more frequent in patients treated with methotrexate–cytarabine plus rituximab and thiotepa, but infective complications were similar in the three groups. The most common grade 3–4 adverse events in all three groups were neutropenia, thrombocytopenia, anaemia, and febrile neutropenia or infections. 13 (6%) patients died of toxicity. Interpretation: With the limitations of a randomised phase 2 study design, the IELSG32 trial provides a high level of evidence supporting the use of MATRix combination as the new standard chemoimmunotherapy for patients aged up to 70 years with newly diagnosed primary CNS lymphoma and as the control group for future randomised trials. Funding: Associazione Italiana del Farmaco, Cancer Research UK, Oncosuisse, and Swiss National Foundation.